2017
DOI: 10.1007/s00198-017-3980-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and physical activity in the prevention and treatment of sarcopenia: systematic review

Abstract: SummaryThis systematic review summarizes the effect of combined exercise and nutrition intervention on muscle mass and muscle function. A total of 37 RCTs were identified. Results indicate that physical exercise has a positive impact on muscle mass and muscle function in subjects aged 65 years and older. However, any interactive effect of dietary supplementation appears to be limited.IntroductionIn 2013, Denison et al. conducted a systematic review including 17 randomized controlled trials (RCTs) to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
312
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(361 citation statements)
references
References 52 publications
6
312
1
9
Order By: Relevance
“…The optimal range remains controversial 38 . Among other consequences, low levels of vitamin D in chronic kidney disease and ESRD cause high bone turnover 39 , muscle weakness, higher risk of falls 40 and high mortality risk 41,42 . The KDOQI guidelines recommend the administration of ergocalciferol and cholecalciferol to patients with CKD stage 3 to 4 if calcidiol levels are below 30 ng/ml 43 but further investigation is needed in order to identify the optimal levels of vitamin D, the appropriate regimen, dose and route of administration 35 .…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…The optimal range remains controversial 38 . Among other consequences, low levels of vitamin D in chronic kidney disease and ESRD cause high bone turnover 39 , muscle weakness, higher risk of falls 40 and high mortality risk 41,42 . The KDOQI guidelines recommend the administration of ergocalciferol and cholecalciferol to patients with CKD stage 3 to 4 if calcidiol levels are below 30 ng/ml 43 but further investigation is needed in order to identify the optimal levels of vitamin D, the appropriate regimen, dose and route of administration 35 .…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…Indeed, it has been reported that, even in individuals that are otherwise considered "healthy", skeletal muscle mass has been shown to decrease~1% per year from its peak occurrence between the ages of 20-30 years old [44]. The loss of skeletal muscle mass is multi-factorial and many factors have been identified as contributors to this event; even though this is not an exhaustive list, a few of these factors are anabolic resistance [45][46][47], apoptosis [48,49], chronic inflammatory signaling associated with long-term, low-grade inflammation [50][51][52][53], and neuromuscular alterations such as motor unit loss that leads to skeletal muscle fiber denervation [45][46][47]. This latter event may be the most consequential, given that it could be thought of in terms of an explicit functional event: loss of motor units results in denervation and loss of skeletal muscle fibers, specifically the fastest skeletal muscle fibers, and finally loss of skeletal muscle function [54].…”
Section: Musculoskeletal Disorders (Msds): Dynapenia Sarcopenia Andmentioning
confidence: 99%
“…It is a cyclical process of death and renewal. Muscle proteins undergo degradation when developing, leading to atrophy [7]. Cells are also subject to apoptosis [1].…”
Section: Sarcopeniamentioning
confidence: 99%
“…However, there are cell renewals after the integration of amino acids. This causes the synthesis of proteins leading to muscular hypertrophy [7]. There is also stimulation of stem cells that lead to the production of satellite cells capable of repairing damaged muscles [4].…”
Section: Sarcopeniamentioning
confidence: 99%